Environmental Impact in the Cultural Output of the Civilizations of Ancient East, Iraq and Eygpt sample (Journal of the College of Education for Women, 2019)
Our research subject (environmental impact in the cultural output of the civilizations of ancient East) the environmental impact on human civilization and how her and adapted to serve in various cultural aspects especially in ancient cultures whether punches or sculptures and other addresses as well as tracing precious stones and raw materials. It was the environment of the civilizations of Mesopotamia and Egypt and another effective impact in drawing ancient history through human interaction and responsiveness. The Iraqi environment was marked by poverty and cruelty on the one hand and on the other cultural elements contributed to the civilization in General and research dealing with technical and product sourcing raw materials, whether inside or outside at various times to Iraq and Egypt and other civilizations in this point to trade and influence The old East and mutual cultural transmission elements of civilization. Without doubt the existence of an enabling environment and good human exploitation leads to authentic civilization thus arose in Mesopotamia and Egypt and other civilizations referred her site was to their surroundings and their appearance in the catalyst role.